VITAMIN D PROFILE OF OUTDOOR PATIENTS PRESENTING WITH ACHES AND PAINS - Idris, Muhammad; Farid, Jamila; Gul, Nasreen (Journal of Ayub Medical College Abbottabad, 2018)
Background: Vitamin D, a fat-soluble vitamin, plays regulatory role in more than 300-800 genes. Daily requirement of vitamin D depends upon the age and exposure to sun. Approximately one billion people in different parts of the world including Pakistan are either Vitamin D deficient or have insufficient levels of vitamin D. The present study, a descriptive cross-sectional study, aimed at knowing the status of vitamin D3 in outdoor patients from Hazara division, having aches and pains. It was conducted over a period of four years on 453 outdoor patients of either sex and all the age groups presenting to Ayub Teaching Hospital. Sample was selected by non-random convenience sampling technique Methods: Common causes of aches and pains other than Vitamin D deficiency were excluded by history, examination and basic laboratory tests. Vitamin D3 estimation was done by immunoassay. Results: Mean age of the participants was 40±19.62 years; the mean level of vitamin D was 21.88±14.12 ng/ml. As much as 398 (87%) participants aged 20-60 years were either vitamin D3 deficient 330 (69.9%), or had vitamin D insufficiency 68 (17.7%). Gender wise, 295 (65%) were females and 158 (35%) males, with female to male ratio of 1.29:1. Normal vitamin D3 level was detected in 55 (12.5%) participants with male predominance. Conclusion: Vitamin D deficiency is alarmingly high in patients presenting with aches and pains, in all age groups, effecting females more than males. Keywords: Vitamin D; Cholecalciferol; Ergocalciferol; Sunlight; Rickets; Osteomalacia